THE PHOTOMETRIC STUDY OF TWO FAINT MIRA-TYPE STARS UX CYG AND AP CYG - Beletskij, Yu. V.; Halevin, A. V.; Kudashkina, L. S. (Одеські астрономічні публікації, 2017)
Two faint Mira-type stars were investigated on the Moscow and Odessa plates collections. The new ephemerids are Tmax = 2426875 + 274d.8 · E for AP Cyg and 2442162+568d · E for UX Cyg. For UX Cyg, the multiharmonic variability was detected. Two stars were suspected in variability among the comparison stars.